Effect of Oral Nutritional Supplementation With and Without Exercise on Nutritional Status and Physical Function of Adult Hemodialysis Patients: A Parallel Controlled Clinical Trial (AVANTE-HEMO Study) - Martin-Alemañy, Geovana; Espinosa-Cuevas, María de los Ángeles; Pérez Vera, Monserrat Gabriela; Wilund, Kenneth R.; Miranda-Alatriste, Paola; Cortés-Pérez, Mario; García-Villalobos, Gloria; Gómez-Guerrero, Irma; Cantú Quintanilla, Guillermo Rafael; Ramírez-Mendoza, Marcelo; Valdez-Ortiz, Rafael (My University, 2020)
Objective: Protein energy wasting affects the nutritional status (NS) and physical function (PF) of dialysis patients. Among the different anabolic strategies to improve NS and PF, oral nutritional supplementation (ONS) and resistance exercise (RE) or aerobic exercise (AE) have been shown to be effective. Nevertheless, the combination of both anabolic strategies has not been completely evaluated. The aim of this study is to assess the effect of exercise combined with ONS versus ONS without exercise during hemodialysis sessions on PF and NS indicators. Methods: Young hemodialysis patients (29 ± 9.3 years) with predominantly unknown causes of renal disease (80%) were divided into the following 3 groups during a period of 12 weeks: (1) ONS (n = 15), (2) ONS + RE (n = 15), and (3) ONS + AE (n = 15). Anthropometric, biochemical, PF, and quality of life measurements were recorded at baseline and after 3 months. Repeated measures analysis of variance and effect sizes (Cohen's d) were used to assess the effect of exercise and nutrition (ISRCTN registry 10251828).